ANALYSIS OF THE DETERMINING METHODS OF THE THERMAL FIRE DETECTORS TIME PARAMETERS - Vasilyeva, О.; Kozak, Y. (Municipal economy of cities. Series: «Economy science», 2023)
The article is devoted to substantiating the pulse method of time parameters determining - the thermal fire detectors' operation time and constant time with a thermal resist sensitive element. Significant research is that the time parameters of thermal fire detectors include the operation time and constant time that are interconnected. It is shown that the contribution of constant time to the operation time can be up to 20% at a speed of change in ambient temperature 0.50C per C-1. It is also found that their testing is used to determine the time parameters of thermal fire detectors, which are divided into stationary or autonomous and operational or object. The article specifies that the disadvantage of inpatient tests with the help of heat chambers is the asymmetry of the airflow distribution and temperature, and the lack of such tests employing standard combustion cells is that the thermal impact parameters on the fire detector sensitive element are not normalized. The research results have found that the amount of the fire detectors' constant time is not determined, and only control of the fire detectors' operation time is carried out according to the admission criteria. During the object tests, in most cases, the thermal impact on a fire detector's sensitive element with the help of small heat chambers is realized, the purpose of such tests is to check the fire detectors' performance without obtaining estimates of their operation time and constant time. It is worth noting that the thermal impact on the fire detector's sensitive element can be carried out with the help of both external and internal sources of heat. The second option is characteristic of fire detectors with a thermal resist sensitive element and is based on the use of the Joule-Lenz effect (heating of a conductor or semiconductor is directly proportional to its resistance, the duration of the current and the square of the current). In this case, new opportunities are opened to improve the efficiency of the fire detectors operation of this type.